Analyse du comportement des structures sous l'effet de la rupture progressive d’une cavité - Billel Bouallag (My University, 2026)
This thesis addresses the analysis of the behavior of surface structures subjected to the effects of the progressive failure of underground cavities, a phenomenon with major geotechnical and structural implications. These cavities, whether of natural or anthropogenic origin, represent a serious threat to the stability of infrastructures, particularly in urban environments. The main objective of this research is to understand the soil deformation mechanisms associated with the formation and evolution of these voids, as well as their impact on surface structures. The study is based on numerical simulations performed using the PLAXIS 2D software, reproducing the effects of the progressive collapse of an underground cavity beneath a surface structure. The numerical model was validated through comparison with Caudron’s experimental approach as well as with empirical methods. A comprehensive parametric study was conducted to analyze the influence of several geometric factors, such as cavity shape (b/a), depth (H/B), and spacing (L/B), on displacements, stress distribution, and the overall stability of the soil–structure system. The results indicate that shallow, narrow, and closely spaced cavities lead to significant ground settlements and localized failures, directly threatening structural safety. Conversely, increased cavity depth and sufficient spacing considerably reduce the associated risks. The numerical approach proved to be reliable, showing good agreement between numerical, experimental, and empirical results, and allows for the identification of critical zones and failure mechanisms. The proposed empirical equations provide a practical predictive tool for estimating displacements as a function of the geometric parameters of underground cavities. This research makes a significant contribution to the understanding of instabilities related to underground cavities and provides useful recommendations for risk prevention and the design of structures in vulnerable areas. --------------------------------------------------------------------------------- تتناول هذه الأطروحة تحليل سلوك المنشآت السطحية المعرّضة لتأثير الانهيار التدريجي للتجاويف الجوفية، وهو أحد الظواهر ذات الانعكاسات الجيوتقنية والإنشائية البالغة الأهمية. وتمثل هذه التجاويف، سواء كانت ذات منشأ طبيعي أو ناتجة عن الأنشطة البشرية، خطرًا حقيقيًا على استقرار البنى التحتية، لا سيما في المناطق الحضرية. وتهدف هذه الدراسة إلى فهم آليات تشوه التربة المرتبطة بتكوّن هذه الفراغات الجوفية وتطورها، وتحليل انعكاساتها على المنشآت المقامة على سطح الأرض. تعتمد هذه الدراسة على نمذجة عددية أُنجزت باستخدام برنامج PLAXIS 2D، حيث تم من خلالها محاكاة تأثير الانهيار التدريجي لتجويف جوفي على منشأة سطحية. وقد جرى التحقق من صحة هذا النموذج العددي بالاستناد إلى المقاربة التجريبية المرجعية لـ Caudron، إضافة إلى المقاربات التجريبية-الاستنباطية. كما أُجريت دراسة معاملية معمّقة لتحليل تأثير عدة عوامل هندسية، من بينها شكل التجويف (b/a)، وعمقه النسبي (H/B)، والمسافة الفاصلة بين التجاويف (L/B)، على الإزاحات، وتوزيع الإجهادات، والاستقرار العام لمنظومة التربة–المنشأة. أظهرت النتائج أن التجاويف الضحلة، الضيقة والمتقاربة تؤدي إلى حدوث هبوطات أرضية كبيرة وانهيارات موضعية، مما يشكل تهديدًا مباشرًا لسلامة المنشآت. في المقابل، فإن زيادة عمق التجاويف وتوفير مسافات كافية بينها يساهمان بشكل ملحوظ في تقليل المخاطر. كما أثبتت الطريقة العددية المعتمدة موثوقيتها، من خلال توافق جيد بين النتائج العددية والتجريبية ، مما يسمح بتحديد المناطق الحرجة وأنماط الانهيار المحتملة. إضافة إلى ذلك، تم اقتراح معادلات تجريبية تتيح التنبؤ بالإزاحات اعتمادًا على المعلمات الهندسية للتجاويف الجوفية. تُسهم هذه الدراسة إسهامًا علميًا مهمًا في تعزيز فهم ظواهر عدم الاستقرار المرتبطة بالتجاويف الجوفية، كما تقدم توصيات عملية ذات قيمة في مجال الوقاية من المخاطر وتحسين تصميم المنشآت في المناطق المعرضة لمثل هذه الظواهر. ---------------------------------------------------------------------------- Cette thèse traite de l’analyse du comportement des structures de surface soumises à l’effet de la rupture progressive des cavités souterraines, un phénomène aux implications géotechniques et structurelles majeures. Ces cavités, qu’elles soient d’origine naturelle ou anthropique représentent un risque sérieux pour la stabilité des infrastructures, notamment en milieu urbain. L’objectif est de comprendre les mécanismes de déformation du sol liés à la formation et à l’évolution de ces vides, ainsi que leur impact sur les ouvrages construits en surface. Cette étude repose sur une simulation numérique réalisée avec le logiciel PLAXIS 2D, reproduisant les effets de la rupture pregressive d’une cavité sur une structure. La validation de cette modélisation a été effectuée en s’appuyant sur l’approche expérimentale de caudron ainsi que sur l’approche empirique.Une étude paramétrique approfondie a permis d’analyser l’influence de plusieurs facteurs géométriques, tels que la forme de la cavité (b/a), sa profondeur (H/B) et son espacement (L/B), sur les déplacements, les contraintes et la stabilité globale du système sol-structure. Les résultats montrent que les cavités peu profondes, étroites et rapprochées provoquent des affaissements importants et des ruptures localisées, menaçant directement la sécurité des structures. À l’inverse, une profondeur accrue et un espacement suffisant entre les cavités réduisent significativement les risques. La méthode numérique s’est révélée fiable, avec une bonne concordance entre les résultats numériques, expérimentaux et empiriques, et permet d’anticiper les zones critiques et les modes de rupture. Les équations empiriques proposées offrent un outil de prédiction des déplacements en fonction des paramètres géométriques des cavités. Cette recherche apporte une contribution significative à la compréhension des instabilités liées aux cavités souterraines, et fournit des recommandations utiles pour la prévention des risques et la conception des structures en zones vulnérables.
Keywords: underground cavities; progressive failure; instability; settlement; soil–structure interaction; numerical modeling; foundation stability; التجاويف الجوفية، الانهيار التدريجي، عدم الاستقرار، الهبوط الأرضي، تفاعل التربة–المنشأة، النمذجة العددية، استقرار الأساسات; cavités souterraines; rupture progressive; instabilité; affaissement; interaction sol-structure; modélisation numérique; stabilité des fondations.